The removal of trace metals at the wastewater treatment plant of Psyttalia - FIRFILIONIS, G.; PARASKEVOPOULOU, V.; VILIOTI, G.; DASSENAKIS, M. (Mediterranean Marine Science, 2004)
The present study investigates the levels of trace metals in the input and output of the Psyttalia wastewater treatment plant, as well as the removal of the various trace metal forms (dissolved, particulate) during primary sedimentation. The trace metals determined were: Pb, Cd, Cu, Zn, Cr, and Ni. The experimental procedure included the collection and analysis of inflow and outflow samples. Dissolved and particulate forms were separated by filtration through 0.45 and 8 Μm Millipore filters and trace metals were determined using atomic absorption spectrometry. The results indicate that particulate matter consists mainly of large particles (> 8 µ m ) and the sedimentation process is more effective in their removal in contrast to smaller particles. The removal of trace metals during primary sedimentation follows the decreasing sequence: Particulate metal in large particles > Particulate metal in small particles > Dissolved metal. Concerning the various metals the removal follows the sequence: Pb ~= Cu>Zn ~= Cr>Cd>Ni. The quantities of trace metals that are discharged to the sea through the outflow pipes of the Psyttalia treatment plant follow the decreasing sequence: Zn >> Cr > Cu > Ni > Pb > Cd.